2022
DOI: 10.3390/ijerph19074127
|View full text |Cite
|
Sign up to set email alerts
|

Are sEMG, Velocity and Power Influenced by Athletes’ Fixation in Paralympic Powerlifting?

Abstract: The bench press is performed in parapowerlifting with the back, shoulders, buttocks, legs and heels extended over the bench, and the use of straps to secure the athlete to the bench is optional. Thus, the study evaluated muscle activation, surface electromyography (sEMG), maximum velocity (MaxV) and mean propulsive velocity (MPV), and power in paralympic powerlifting athletes under conditions tied or untied to the bench. Fifteen experienced Paralympic powerlifting male athletes (22.27 ± 10.30 years, 78.5 ± 21.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Thus, the evaluation of an athlete's training status and initial condition is the crucial point for the correct elaboration of a training program to be applied in different phases of the sports preparation [11]. In these initial conditions, some training variables are manipulated to prescribe and control resistance training programs such as: sets, time intervals, position and intensity [11][12][13]. On the other hand, in these initial conditions, there are possible disparities between different training methods to determine mechanical outputs in strengthpower exercises.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the evaluation of an athlete's training status and initial condition is the crucial point for the correct elaboration of a training program to be applied in different phases of the sports preparation [11]. In these initial conditions, some training variables are manipulated to prescribe and control resistance training programs such as: sets, time intervals, position and intensity [11][12][13]. On the other hand, in these initial conditions, there are possible disparities between different training methods to determine mechanical outputs in strengthpower exercises.…”
Section: Introductionmentioning
confidence: 99%
“…Seven studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ] were excluded with reason ( n = 2, not reporting sufficient details; n = 5, not disaggregating data according to para-sports discipline). Finally, 37 studies [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ] were retained in the present scoping review. We found that the included studies focused on a range of aspects involving health, classification, the etiology of injuries, and performance.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] investigated the biomechanics of BP in PP, including the performance of PP under two different BP conditions (namely, with the legs tied and untied [ 34 , 35 ]), the impact of the choice of a specific grip width [ 36 , 37 ], the effects of arched and flat techniques [ 38 ], the impact of a partial vs. full range of movement (ROM) training [ 39 ], the evaluation of strength and muscle activation indicators in sticking point region [ 40 ], and the force output during different phases of the PP BP movement [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations